2021
DOI: 10.1002/berj.3751
|View full text |Cite
|
Sign up to set email alerts
|

Sexting and institutional discourses of child protection: The views of young people and providers of relationship and sex education

Abstract: This article focuses on discourses of child safety and protection of stakeholder organisations (SOs) and school pastoral care co‐ordinators (PCCs) on educating young people about sexting. Individual semi‐structured interviews were conducted with the representatives of four organisations who assist schools in the delivery of Relationships and Sexuality Education (RSE); and with three PCCs in three different types of secondary schools in Northern Ireland to ascertain how their school educates and responds to sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Many students are disappointed with the school sex education they receive (e.g., Advocates for Youth, 2022; Karp, 2021;York et al, 2021). At the same time, there remains an urgent need for school sex education (e.g., Ofsted, 2021;Ringrose et al, 2021;Srinivasan, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Many students are disappointed with the school sex education they receive (e.g., Advocates for Youth, 2022; Karp, 2021;York et al, 2021). At the same time, there remains an urgent need for school sex education (e.g., Ofsted, 2021;Ringrose et al, 2021;Srinivasan, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, although RSE is a statutory element of the Northern Irish curriculum, the guidelines allow schools latitude for interpretation in accordance with the Christian ethos of the school. The result is poor and inconsistent RSE (McBride & Schubotz, 2017; York, 2019; York et al., 2021a, b).…”
Section: Introductionmentioning
confidence: 99%
“…The Rugby Rape Trial revealed the inadequacy of the criminal justice system to deal with such allegations and exposed how sexual violence, misogyny and sexism are framed and processed in law, education, the church and wider society (Killean et al., 2021). The school system is segregated along largely Protestant and Catholic lines and is deeply influenced by a Christian ethos in which sex education is barely discussed, and then only in terms of biology, the virtue of abstinence and the idea that sex is for marriage (York et al., 2021a, b). The moral conservatism of the province has led to attitudes of shame and stigma about sex, sexuality, sexual violence and reproductive rights (York et al., 2021a, b; Flanagan, forthcoming).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently published governmentsponsored reports by the Department of Justice and Department of Communities have called for compulsory standardized RSE in order to tackle sexual offences (Gillen, 2019), actively promote LGBTQIA+ inclusivity (The Sexual Orientation Strategy Expert Advisory Panel, 2021), and to dismantle normative, societal gendered expectations (Gray et al, 2021). While few studies have specifically focused on how national policy actors within Northern Ireland have conceptualized the debate around RSE (Wilkinson, 2017), the sexual attitudes and behaviors of Northern Irish young people (McBride & Schubotz, 2017;York et al, 2021), and increased LGBTQ+ bullying in schools (NISRA, 2016), missing from social policy literature is a feminist lens that centrally focuses on the examination of RSE policy content, specifically content and dominant discourses related to gender and sexual diversity.…”
Section: Introductionmentioning
confidence: 99%